International Responses to Mass Atrocities in Africa : Responsibility to Protect, Prosecute, and Palliate - Mills, Kurt (Book collections on Project MUSE., 2015)
In International Responses to Mass Atrocities in Africa, Kurt Mills develops a typology of responses to mass atrocities, investigates the limitations of these responses, and calls for such responses to be implemented in a more timely and thoughtful manner.